ANALISIS SISTEM ANTRIAN SINGLE CHANEL-MULTIPHASE DALAM PENINGKATAN EFISIENSI WAKTU PELAYANAN PADA PELAYANAN MEDICAL CHECK-UP DI RUMAH SAKIT - Zaky, Abdul; Suryandartiwi, Wiwik; Bagiana, Rizka (LPPM Universitas Awal Bros, 2023)
Medical Check-Up (MCU) service facilities must of course be available in a hospital. As for providing the best MCU service, the Hospital must provide the best time service for those who are queuing to get the MCU results. The purpose of this study was to determine the queuing system, standardization of service time, and patient perceptions of MCU service time at the Hospital. The system Matic sampling method is used in selecting the sampling in the research conducted. The number of samples observed was 21 people consisting of MCU examination patients. The data were obtained through the process of observation and literature study, then distributing questionnaires and collecting documentation. Test data used includes data processing and data analysis. The queuing system used by the MCU service is a single-channel-multiphase system that is effectively implemented. This system is a queuing system that applies the principle of first come first serve (FCFS). The first come first serve (FCFS) queue discipline increasingly provides a sense of fairness for every visitor who queues to get MCU results. The standardization of MCU service time was declared in the slow category because the Minimum Service Standardization was 85.24 minutes, which was 25.2 minutes different from the medium SPM category, which was 60 minutes. Based on the 17-point statements of patient perceptions of the Hospital's MCU queue system with the Strongly Agree and Agree categories. The percentage of the patient's agreement value on each statement is above 50%. This shows that the patient's perception of the MCU queue service at the Hospital is good, but does not really have additional value because it is still quite common in Hospitals.